PELAKSANAAN PENDAFTARAN PERALIHAN HAK MILIK ATAS TANAH KARENA JUAL BELI SETELAH PEMEKARAN KANTOR PERTANAHAN KOTA SURABAYA BERDASARKAN PERATURAN KEPALA BADAN PERTANAHAN NASIONAL NOMOR 16 TAHUN 2010 - , ENDAH TRIMAWARNI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research titled âThe Enforcement of Land Property Transfer Application Due to Transaction After Expansion of Surabaya City Land Office Based on National Land Head Regulation Based on National Land Body Regulation Number 16 of 2010â was aimed to know the enforcement of land property transfer application due to transaction after the expansion of Land Office of Surabaya City, and to know the completion time of land property transfer completion due to transaction after the expansion of Land Office of Surabaya City. This was a judiciary empirical research that was an approach method by examining law applied and also what was actually going on in the community. Data gathering was conducted by a field research to obtain a primary data and bibliography research to obtain a secondary data. The research result was analyzed quantitatively by selecting data, classifying data, connecting data with norms and principles so that obtained a clear illustration related to problems observed. The data research result showed that after expansion of Surabaya City Land Office, work area of Surabaya City PPAT was divided into 2 offices namely: 1st Surabaya City PPAT with its work area was 1st Surabaya City Land Office covered 16 districts and 2nd Surabaya City PPAT covered 15 districts. The requirements of land property transfer application due to transaction after expansion of Surabaya City Land Office did not change significantly compared with before expansion of the Land Office so that the purpose of Surabaya City Land Office expansion was not completely achieved. The problems faced in land property transfer completion time due to transaction in Surabaya City Land Office namely: by correcting old documents and the documents was returned due to deficiency or there was a transaction act correction. The effort conducted to overcome was by firstly examining a transaction act and documents required and The Land Office was expected to change in its service bureaucracy system and employeeâs performance quality.